Free throw and outcomes: Pilot study on intensive training versus extensive one - Altavilla, G.; D'Isanto, T.; Di Tore, P. A.; Raiola, G. (Journal of Human Sport & Exercise, 2018)
Free throw is a fundamental of the basketball that can be trained under the same match conditions, as there is no interference of the defense in the attempt to make a point. It is a fundamental that theoretically has the highest degree of efficiency, so it is useful to know which specific training method allows the best possible performance. The aim of the present study is to evaluate the difference in yields (results) on free throws in basketball through the intensive and extensive training method. The method is experimental and the study was conducted on a sample of 24 male athletes (10-12 years) divided into two experimental groups of 12 young athletes each. To them it was assigned of the free throw motor task by the regulatory position. Participants were initiated at learn the new motor task, using two different training methods: intensive method with the same number of throws in a period of 3 days a week and extensive method with the same number of throws in a period of dual time. Each group done 2280 throws per week for four weeks. Group A has conducted training on days six consecutive weekly, while Group B on days three consecutive weekly. They have been collected data of the throws realized individual and of group. The result for Group A (extensive training) resulted in an increase the performance by 8.53%. The result for Group B (intensive training) resulted in an increase the performance lower than Group A and was 3.21%. Group A had a steady increase in performance over the four weeks, while Group B have had a limited improvement in performance. The final percentage difference between the two groups has been 5.23%. Improvement of the B Group, with Intensive Training, in the four weeks of the learning period it has been less congruous than the one with the extensive training of Group A. After the first week, the results show the absence of significant differences between the two groups p-value = 0.257 (p> 0.05); instead, after four weeks, the results show a significant difference between the two samples p-value = 0.01 (p <0.05). Finally, from results apparead that extensive practice, in the realization of effective and consolidated motor learning, must be based on careful time distribution of the exercises and with a high number of repetitions in order to obtain high precision and an elevated stability of the performance.